Evaluation of Serum Phosphorylated Neurofilament Subunit NF‐H as a Prognostic Biomarker in Dogs With Thoracolumbar Intervertebral Disc Herniation. Issue 3 (27th January 2014) - Nishida, Hidetaka; Nakayama, Masanari; Tanaka, Hiroshi; Kamishina, Hiroaki; Izawa, Takeshi; Hatoya, Shingo; Sugiura, Kikuya; Suzuki, Yoshihisa; Ide, Chizuka; Inaba, Toshio
<x xml:space="preserve">Abstract</x> Objective To investigate whether pNF‐H is a prognostic biomarker of spinal cord injury (SCI) in paraplegic dogs with thoracolumbar intervertebral disc herniation (IVDH). Study Design Prospective, case‐control clinical study Animals Dogs (n = 60) with SCI from IVDH and 6 healthy dogs. Methods Serum from 60 thoracolumbar IVDH dogs (Grade 4: 22 dogs; Grade 5: 38 dogs) collected 1–3 days after injury, and 6 control dogs, was analyzed using enzyme‐linked immunosorbent assay (ELISA) against a phosphorylated form of the high‐molecular‐weight neurofilament subunit NF‐H (pNF‐H). Serum pNF‐H levels were compared between different IVDH grades and their prognostic value was investigated. Results pNF‐H levels were significantly greater in Grade 5 than Grade 4 dogs. There were significant differences in pNF‐H levels between dogs that regained voluntarily ambulation and those that did not. All 8 dogs that had high pNF‐H levels 1–3 days after injury did not regain the ability to walk after surgery. Conclusions Serum pNF‐H levels might be a biomarker for predicting prognosis of canine SCI.